2007
DOI: 10.1038/sj.npp.1301309
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding Effects and Reinstatement of MDMA-Induced CPP in Adolescent Mice

Abstract: Although the rewarding effects of 3,4-methylenedioxy-metamphetamine (MDMA) have been demonstrated in self-administration and conditioned place preference (CPP) procedures, its addictive potential (ie, the vulnerability to relapse, measured by its ability to induce reinstatement of an extinguished response), remains poorly understood. In this study, the effects of MDMA (5, 10, and 20 mg/kg) on the acquisition, extinction and reinstatement of CPP were evaluated in mice, using two different protocols during acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
44
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 60 publications
11
44
0
1
Order By: Relevance
“…La reinstauración se refiere a la recuperación de la respuesta aprendida o condicionada y supone un nuevo aprendizaje de la asociación entre el efecto reforzante de la sustancia y las claves ambientales después de la extinción Do Couto et al, 2006;Do Couto, Aguilar, Lluch, Rodríguez-Arias y Miñarro, 2009;García-Pardo et al, 2014, 2015a, 2015b. La reinstauración puede estar inducida por diferentes factores bien farmacológicos, físi-cos o sociales, como por ejemplo la re-exposición a una dosis baja de la droga con la que se adquirió el condicionamiento, conocida como dosis priming (Cruz, Marín y Planeta, 2008;Daza-Losada et al, 2007), o la exposición a una situación estresante como un shock eléctrico en las patas (Bossert, Marchant, Calu y Shaham, 2013) o como la derrota en un encuentro agonístico (García-Pardo et al, 2014;2015b;Shaham et al, 2003;Shalev, Grimm y Shaham, 2002;Tzschentke, 2007).…”
Section: 2condicionamiento De Preferencia De Lugar (Cpl)unclassified
“…La reinstauración se refiere a la recuperación de la respuesta aprendida o condicionada y supone un nuevo aprendizaje de la asociación entre el efecto reforzante de la sustancia y las claves ambientales después de la extinción Do Couto et al, 2006;Do Couto, Aguilar, Lluch, Rodríguez-Arias y Miñarro, 2009;García-Pardo et al, 2014, 2015a, 2015b. La reinstauración puede estar inducida por diferentes factores bien farmacológicos, físi-cos o sociales, como por ejemplo la re-exposición a una dosis baja de la droga con la que se adquirió el condicionamiento, conocida como dosis priming (Cruz, Marín y Planeta, 2008;Daza-Losada et al, 2007), o la exposición a una situación estresante como un shock eléctrico en las patas (Bossert, Marchant, Calu y Shaham, 2013) o como la derrota en un encuentro agonístico (García-Pardo et al, 2014;2015b;Shaham et al, 2003;Shalev, Grimm y Shaham, 2002;Tzschentke, 2007).…”
Section: 2condicionamiento De Preferencia De Lugar (Cpl)unclassified
“…We hypothesized that MDMA choice would be increased by elevating the ambient temperature and decreased by lowering the ambient temperature. Few studies have examined MDMA-induced reinstatement (Morley et al 2004;Daza-Losada et al 2007) and none have examined the ability of MDMA to reinstate responding previously maintained by MDMA. Reinstatement is often used as a model of relapse or craving (for review, see Shaham et al 2003); however, recent studies have suggested that the discriminative stimulus effects of drugs have a prominent role in increasing extinguished responding (Odum and Shahan 2004;Cador et al 2006;Banks et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Since no neurotoxic effects were observed after any of the drug pretreatments measured in the first reinstatement test, our results could be explained by the fact that ethanol increases the concentration of MDMA in the brain. Indeed, we found that the rewarding effects of MDMA produced an inverted U-curve in function of dose, with high doses proving to be devoid of motivational effects (Daza-Losada et al, 2007).…”
Section: Mdma and Ethanol Bingesmentioning
confidence: 99%
“…None of the drugs, whether administered alone or together, induced significant changes in the concentration of these monoamines in the striatum, cortex or hippocampus 3 weeks later, at which time CPP was initiated (Daza-Losada et al 2008b). Moreover, the chosen CPP schedule did not affect the concentration of monoamines (Daza-Losada et al 2007). Fig.…”
Section: Mdma Plus Cocainementioning
confidence: 99%